OS12.1 Editing of IDH1 R132H mutation in human induced pluripotent stem cells to investigate tumor genesis in glioma. (6th September 2019) - Köpp, A; Preussler, M; Richter, S; Heide, M; Marrone, L; Sterneckert, J; Schöler, A; Capper, D; Schröck, E; Klink, B
Abstract: BACKGROUND: Low grade gliomas and secondary glioblastomas are characterised by a hot-spot mutation in the Isocitrate dehydrogenase 1 (IDH1). The mutation causes a new catalytic function of the enzyme resulting in the production of 2-Hydroxyglutarat (2-HG), which is known as an oncometabolite. To this day, the pathomechanism by which IDH1 mutation promotes tumorigenesis is not completely understood and the tumour cell of origin for glioma is not known. Moreover, reliable cell models reflecting the patient ́s situation are not available. Thus, we aim at creating human induced pluripotent stem cells (hiPSC) carrying the IDH1 R132H mutation. We will utilize this cell model to investigate how the mutation influences stem cell properties and cell differentiation in neuronal progenitor cells. MATERIAL AND METHODS: For designing the cell model, we applied the novel CRISPR/Cas9 based genome editing tool Base Editor 3 and 4. We transiently transfected the cells with two plasmids containing the Cas9 enzyme and sgRNA respectively. To determine editing efficiency, cells were investigated using the T7 Endonuclease 1 assay and Next Generation Sequencing. Single cell clones were picked to analyse allele status using allele-specific PCR with subsequent Sanger Sequencing. RESULTS: Using fluorescence-activated cell sorting we measured a transfection efficiency in iPSCs for one plasmid of 33.8% ± 5.92%. Out of 96 picked clones one clone showed the IDH1 mutation. Thus, the overall editing efficiency was about 1%. We confirmed expression of mutated IDH1 R132H by Western Blot. Measurement of the tricarboxylic acid cycle metabolites using liquid chromatography tandem mass spectrometry (LC-MS/MS) showed a forty times increased concentration of 2-HG in IDH-mutated compared to the wildtype iPSCs, proving that the mutated enzyme is functional. To investigate effects of the IDH1 R132H on cell differentiation, we generated cerebral organoids from our iPSC-models. The IDH1 R132H mutation did not inhibit the cell differentiation in maturation of cerebral organoids. However, we observed differences in the growth between mutated and wildtype brain organoids. We additionally characterized our cell models using genome wide methylation arrays and RNA-Seq; these results will also be presented. CONCLUSION: We successfully established a heterozygous IDH1 R132H mutated hiPSC cell line, which represents a promising cell model for future studies of early glioma genesis.